Strategi Pengembangan Sumber Daya Manusia dalam Meningkatkan Profesionalisme Anggota Polres Bengkayang pada Pelayanan Publik di Era Digitalisasi - Tri Teguh Mulyono; Lina Sunyata; Arifin Arifin (Policy, Law and Political Research Center, 2026)
This study aims to describe and analyze human resource development strategies for enhancing the professionalism of Bengkayang Police Department personnel in public service in the era of digitalization. The study employs a descriptive method with a qualitative approach. Data collection was conducted through interviews and document analysis using interview guidelines and a document analysis framework. Human resource development strategies were analyzed through the aspects of HR development needs assessment, planning and design of HR development programs, and implementation of HR development programs. The results of the study indicate that HR development needs assessment at the Bengkayang Police Department has not been optimally implemented due to existing gaps in information technology proficiency, limitations in competency-based training, and weak mapping of personnel competency needs. The planning and design of HR development programs have been carried out through the preparation of annual work plans; however, they still need to be strengthened through a competency-based approach, integration with the performance evaluation system, and adequate support in terms of facilities and infrastructure. The implementation of the human resource development program has been proceeding quite well through the placement of personnel based on competencies and the principle of meritocracy, but it still requires further development through training accompanied by practical application, assessment of learning outcomes, continuous mentoring, and management innovation. Therefore, strengthening is required.